2020
DOI: 10.1111/joss.12625
|View full text |Cite
|
Sign up to set email alerts
|

Surfacing consumer psychosensory perceptions of a nonendemic food: The case of coffee in a tea culture

Abstract: Introducing a culturally unfamiliar food to a new market requires understanding local meaning. Local psychological associations with nonendemic food often remain masked from common research methods such as surveys and home interviews. We apply a localized adaptation of the Zaltman Metaphor Elicitation Technique to explore consumer psychosensory perceptions of nonendemic foods—the contemporary phenomenon of coffee's acceptance in Taiwan's tea‐dominated market. A purposive sample of 10 trial and 20 full study pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Many studies within the disciplines of marketing and consumer psychology attempt to provide evidence that consumer behaviour, being the decision-making process of the consumer and their subsequent evaluation of products or services, can be influenced by past or present sentiments or events related to the nation-state, whether political, economic or social (Loxton et al, 2020;Deli-Gray et al, 2013;Viktoria Rampl et al, 2012). Whilst consumer attitudes towards domestic or imported goods are often believed to evolve slowly (Karimov and El-Murad, 2019), perceptions of a country, its people and its products can evolve quickly in response to rapidly changing sociopolitical or socio-economic actions, thereby rapidly changing consumer behaviours towards goods originating where periods of turmoil are occurring (Caskey et al, 2020). Such consumer affinity or animosity towards domestic or foreign products and the factors that facilitate them has received considerable attention within literature over time (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies within the disciplines of marketing and consumer psychology attempt to provide evidence that consumer behaviour, being the decision-making process of the consumer and their subsequent evaluation of products or services, can be influenced by past or present sentiments or events related to the nation-state, whether political, economic or social (Loxton et al, 2020;Deli-Gray et al, 2013;Viktoria Rampl et al, 2012). Whilst consumer attitudes towards domestic or imported goods are often believed to evolve slowly (Karimov and El-Murad, 2019), perceptions of a country, its people and its products can evolve quickly in response to rapidly changing sociopolitical or socio-economic actions, thereby rapidly changing consumer behaviours towards goods originating where periods of turmoil are occurring (Caskey et al, 2020). Such consumer affinity or animosity towards domestic or foreign products and the factors that facilitate them has received considerable attention within literature over time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…, 2012). Whilst consumer attitudes towards domestic or imported goods are often believed to evolve slowly (Karimov and El-Murad, 2019), perceptions of a country, its people and its products can evolve quickly in response to rapidly changing socio-political or socio-economic actions, thereby rapidly changing consumer behaviours towards goods originating where periods of turmoil are occurring (Caskey et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…First, meta-analytical research shows that most studies of GIL were conducted in European countries, Australia and New Zealand, or on the American continent (US, Chile, Argentina) (Santeramo and Lamonaca, 2020), but this research provides a case from east Asia. Additionally, tea is the target agricultural product in the current study and is highly integrated into East Asia, where olive oil and wines do not play as important a role as in European countries but tea is a mainstream (Caskey et al , 2021). Meta-analytical studies have revealed that a price premium exists across different studies, i.e.…”
Section: Introductionmentioning
confidence: 99%